Overexpression of HER-2/neu Oncogene and Transitional Cell Carcinoma of Bladder - Jalali Nadoushan, Mohammad Reza; Taheri, Touraj; Jouian, Neda; Zaeri, Farid (Urology Journal, 2009)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!-- /* Font Definitions */ @font-face {font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:1; mso-generic-font-family:roman; mso-font-format:other; mso-font-pitch:variable; mso-font-signature:0 0 0 0 0 0;} @font-face {font-family:Tahoma; panose-1:2 11 6 4 3 5 4 4 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:1627400839 -2147483648 8 0 66047 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman","serif"; mso-fareast-font-family:"Times New Roman";} p.CharCharCharChar, li.CharCharCharChar, div.CharCharCharChar {mso-style-name:" Char Char Char Char"; mso-style-unhide:no; margin-top:0cm; margin-right:0cm; margin-bottom:8.0pt; margin-left:0cm; line-height:12.0pt; mso-line-height-rule:exactly; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Tahoma","sans-serif"; mso-fareast-font-family:"Times New Roman"; mso-bidi-font-family:"Times New Roman";} .MsoChpDefault {mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt;} @page Section1 {size:612.0pt 792.0pt; margin:72.0pt 72.0pt 72.0pt 72.0pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <![endif]--> Introduction: The aim of this study was to evaluate the relationship between HER-2/neu oncogene expression and grade of transitional cell carcinoma (TCC) of the bladder. Materials and Methods: In this cross-sectional study, 75 formalin-fixed paraffin-embedded specimens of primary TCC of the bladder were stained with a monoclonal antibody against HER-2/neu oncoprotein. Another section was stained by hematoxylin-eosin and the tumor grade was determined according to the World Health Organization/International Society of Urological Pathologists criteria. Results: Tumor specimens belonged to 49 men (65.3%) and 26 women (34.7%) with a mean age of 56.3 Â± 9.1 years (range, 39 to 80 years). The tumor grades were 1, 2, and 3 in 14 (18.7%), 35 (46.7%), and 26 (34.7%) specimens, respectively. A total of 28 (37.3%) patients were positive for overexpression of HER-2/neu. There were 1 case of HER-2/neu-positive (7.1%) with a grade 1 tumor, 10 (28.6%) with grade 2, and 17 (65.4%) with grade 3; a significant relationship between HER-2/neu overexpression and grade of the bladder TCC tumors was found (P = .002). Conclusion: Expression of HER-2/neu oncogene has a direct relationship with the grade of the bladder TCC. Further studies with longer follow-up period and a larger sample size can determine the probable role of HER-2/neu expression as a prognostic factor in the TCC of bladder.